Th17 cytokines differentiate obesity from obesity‐associated type 2 diabetes and promote TNFα production. (18th November 2015) - Ip, Blanche; Cilfone, Nicholas A.; Belkina, Anna C.; DeFuria, Jason; Jagannathan‐Bogdan, Madhumita; Zhu, Min; Kuchibhatla, Ramya; McDonnell, Marie E.; Xiao, Qiang; Kepler, Thomas B.; Apovian, Caroline M.; Lauffenburger, Douglas A.; et al.
Abstract : Objective: T cell inflammation plays pivotal roles in obesity‐associated type 2 diabetes (T2DM). The identification of dominant sources of T cell inflammation in humans remains a significant gap in understanding disease pathogenesis. It was hypothesized that cytokine profiles from circulating T cells identify T cell subsets and T cell cytokines that define T2DM‐associated inflammation. Methods: Multiplex analyses were used to quantify T cell‐associated cytokines in αCD3/αCD28‐stimulated PBMCs, or B cell‐depleted PBMCs, from subjects with T2DM or BMI‐matched controls. Cytokine measurements were subjected to multivariate (principal component and partial least squares) analyses. Flow cytometry detected intracellular TNFα in multiple immune cell subsets in the presence/absence of antibodies that neutralize T cell cytokines. Results: T cell cytokines were generally higher in T2DM samples, but Th17 cytokines are specifically important for classifying individuals correctly as T2DM. Multivariate analyses indicated that B cells support Th17 inflammation in T2DM but not control samples, while monocytes supported Th17 inflammation regardless of T2DM status. Partial least squares regression analysis indicated that both Th17 and Th1 cytokines impact %HbA1c. Conclusions: Among various T cell subsets, Th17 cells are major contributors to inflammation and hyperglycemia and are uniquely supported by B cells in obesity‐associated T2DM.